Acute Lower Gastrointestinal Bleeding - Navuluri, Rakesh; Kang, Lisa; Patel, Jay; Van Ha, Thuong (Seminars in Interventional Radiology, 2012)
The annual incidence of lower gastrointestinal bleeding (LGIB) is ∼20.5 in 100,000 in the general Western population and results in 1 to 2% of hospital emergencies. When medical management and endoscopic therapy are inadequate in cases of acute LGIB, endovascular intervention can be lifesaving. In these emergent situations it is important for the interventional radiologist to be well versed in the multidisciplinary preangiographic work-up, the angiographic presentations of LGIB, and the endovascular therapeutic options. We describe a case of LGIB managed with endovascular embolization and detail the angiographic techniques used, followed by a detailed discussion of the various treatment approaches to LGIB.
Keywords: embolization; GI bleeding; emergent